Remote sensing applied to mapping, identification and analysis of land use in the city of Garanhuns-PE - Deus, Rodolfo Alexandre da Silva Gomes de; Ramos, Renilson Pinto da Silva; Costa, Samuel Othon de Souza; Gomes, Daniel Dantas Moreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In this paper the objective is to use remote sensing for identification and mapping of certain areas, seeking to identify such areas to demonstrate the possibilities of a larger organization in the county analyzed. The study is based on Garanhuns municipality, located in the federal unit of Pernambuco. Remote sensing provides greater objectivity, thus making identification of the analyzed areas easier, and provide a greater amount of data for a variety of analyzes, thus providing the basis for future work, which have the same objective of a larger organization area. To identify the composition RGB (Red, green, and blue) fused with the panchromatic band was utilized, so that it has a higher spatial resolution, that facilitates the identification which is intended to have, the fostering of the data, we used the satellite image acquired by Landsat-8, provided by the USGS, such images were treated with 10.2.2 ArcGIS software, aiming to extract the greatest possible amount of information for better treatment of the data analyzed.